Kajian Literatur tentang Teknik Tata Rias Wajah dan Pengaruhnya terhadap Hasil Riasan - Anik Maghfiroh; Hidayah Desti Khayrunnisa; Meiliza Nur Shela; Nia Selvi Ayu Saputri; Siltya Yekti Hasna Larosa; Gracia Mulianov Alnatares (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
Makeup artistry is an aesthetic skill that functions to enhance appearance while concealing facial imperfections. Techniques such as foundation selection, foundation mixing, contouring, and natural makeup application have been proven to influence the quality of makeup results, both in terms of durability and aesthetics. This study employs a literature review method by examining several national and international journals related to makeup techniques. The findings indicate that selecting the appropriate type of foundation and applying mixing techniques can extend makeup durability for more than two hours. Furthermore, daily makeup practice significantly improves practical skills within society, while basic knowledge of cosmetics shows a positive correlation with the proper use of cosmetic products. This review emphasizes that makeup techniques have a tangible impact on the quality of results, whether in educational contexts, professional practice, or everyday needs. Therefore, mastering both theoretical and practical aspects of makeup artistry is essential for the sustainable development.